2022
DOI: 10.3390/toxins14020124
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Specific Holin-Mediated Mechanism Facilitates the Secretion of Lethal Toxin TcsL in Paeniclostridium sordellii

Abstract: Protein secretion is generally mediated by a series of distinct pathways in bacteria. Recently, evidence of a novel bacterial secretion pathway involving a bacteriophage-related protein has emerged. TcdE, a holin-like protein encoded by toxigenic isolates of Clostridioides difficile, mediates the release of the large clostridial glucosylating toxins (LCGTs), TcdA and TcdB, and TpeL from C. perfringens uses another holin-like protein, TpeE, for its secretion; however, it is not yet known if TcdE or TpeE secreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…The T10SS-mediated release of Tc toxins also fits well into the emerging paradigm of anti-eukaryotic toxin export by phage-derived proteins ( 48 ). Notable examples include release of the Clostridium difficile toxins A and B via a holin and endolysin ( 56-58 ), the holin-dependent export of large clostridial glucosylating toxins ( 59, 60 ) and the endolysin-dependent secretion of typhoid toxin ( 61 ). Notably, in all the cases described above, the current consensus is that the holin and/or endolysin-mediated export occurs via a non-lytic mechanism ( 48, 56, 59-61 ), although in light of the data presented here the potential use of suicidal soldier cell subpopulations also by these pathogens is a fascinating possibility that is worth investigating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The T10SS-mediated release of Tc toxins also fits well into the emerging paradigm of anti-eukaryotic toxin export by phage-derived proteins ( 48 ). Notable examples include release of the Clostridium difficile toxins A and B via a holin and endolysin ( 56-58 ), the holin-dependent export of large clostridial glucosylating toxins ( 59, 60 ) and the endolysin-dependent secretion of typhoid toxin ( 61 ). Notably, in all the cases described above, the current consensus is that the holin and/or endolysin-mediated export occurs via a non-lytic mechanism ( 48, 56, 59-61 ), although in light of the data presented here the potential use of suicidal soldier cell subpopulations also by these pathogens is a fascinating possibility that is worth investigating.…”
Section: Discussionmentioning
confidence: 99%
“…Notable examples include release of the Clostridium difficile toxins A and B via a holin and endolysin ( 56-58 ), the holin-dependent export of large clostridial glucosylating toxins ( 59, 60 ) and the endolysin-dependent secretion of typhoid toxin ( 61 ). Notably, in all the cases described above, the current consensus is that the holin and/or endolysin-mediated export occurs via a non-lytic mechanism ( 48, 56, 59-61 ), although in light of the data presented here the potential use of suicidal soldier cell subpopulations also by these pathogens is a fascinating possibility that is worth investigating. Finally, combining the observation that YenTc deletion causes full loss of Y. entomophaga virulence ( 22 ) with our discovery that Tc toxins are produced by only few cells in a population leads to the startling insight that pathogen virulence can be determined by a small number of specialized soldier cells.…”
Section: Discussionmentioning
confidence: 99%
“…All holins that are genetically associated with the known large clostridial toxins are able to transport endolysins and are therefore bona fide holins [ 40 ][ 37 ][ 41 ][ 42 ]. In case of the holin TcdE, its phage origin could be traced back, and remnants of the associated endolysin gene have been found in direct vicinity of tcdE in the PaLoc of C. difficile [ 40 ].…”
Section: Non-lytic Holin-mediated Transport Is Involved In the Releas...mentioning
confidence: 99%
“…The holin specifically is required for the toxin transport, and as recombinant TpeE alone sufficed for TpeL secretion, it has been suggested that the holin may transport the toxin directly [ 42 ]. Also the holin of P. sordellii has been found to specifically promote toxin release in that organism [ 41 ]. It has not been shown directly that the toxins themselves are transported by the respective holins, which is why the authors carefully claimed only a function in the release of the toxin, but, like in the case of C. difficile , the toxins lack signal peptides for Sec transport, are genetically linked to holins on pathogenicity loci, and there are no known alternative pathways for the non-lytic release of folded proteins in these clostridia.…”
Section: Non-lytic Holin-mediated Transport Is Involved In the Releas...mentioning
confidence: 99%
See 1 more Smart Citation